2004
DOI: 10.1111/j.1447-0594.2004.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Filial piety revisited in the context of modernizing Asian societies

Abstract: This paper discusses the concept of filial piety in the context of social changes in Asia, in particular Singapore. The changing meaning and expression of this concept, which is also a cultural value, has to be researched by Asian gerontologists. The empirical research in Singapore shows that while this concept is still considered important its definition is shifting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…In this study conducted in an Asian setting, caregivers who were the children of care-recipient may have answered questions on ZBI more positively as they may have perceived it being viewed favourably by others as being filial. In Asian societies, providing care and financial support to one’s parents is considered one of the critical components of filial piety [ 63 ]. To reduce this bias, interviewers reassured all participants that there were no right or wrong answers and were instructed to answer all questions based on their first instinct to minimise the effect of elucidating socially desirable responses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study conducted in an Asian setting, caregivers who were the children of care-recipient may have answered questions on ZBI more positively as they may have perceived it being viewed favourably by others as being filial. In Asian societies, providing care and financial support to one’s parents is considered one of the critical components of filial piety [ 63 ]. To reduce this bias, interviewers reassured all participants that there were no right or wrong answers and were instructed to answer all questions based on their first instinct to minimise the effect of elucidating socially desirable responses.…”
Section: Discussionmentioning
confidence: 99%
“…Research on Western families has indicated that grandparental involvement could help to share responsibility for child-care, and could provide emotional support to decrease the level of parental stress (Lee & Gardner, 2010). Chinese families tend to have a strong bond with their extended families, and also value the filial piety to the elderly which all family members should respect and obey (Mehta & Ko, 2004). Therefore, input from the older generation can add extra stress to the parents of the child with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Filial piety tenets focus on maintaining family order by promoting responsibility, interdependence, sacrifice, and family harmony (Bengtson & Putney, ). Despite increasing pressure to value independence and autonomy with the Westernization of modern Chinese societies (Yue & Ng, ), contemporary Chinese individuals still endorse the filial duties of respecting, loving, and honoring parents, as well as providing material support and eventual care to elderly parents to some degree (Laidlaw, Wang, Coelho, & Power, ; Mehta & Ko, ). Adolescents' filial piety beliefs and behaviors are related to, but distinct from the general quality of their parent–child relationship (Cheah, Bayram Özdemir, & Leung, ).…”
Section: Filial Piety Among the Chinese: Traditional And Contemporarymentioning
confidence: 99%
“…Parents are expected to sacrifice time and money for their children as an investment in their future and also to internalize feelings of veneration and indebtedness in their children. These feelings of indebtedness in children are believed to motivate children to repay their parents' sacrifice and investments by helping and supporting them (Bengtson & Putney, ; Cheah et al., ; Mehta & Ko, ). Thus, this dilemma was designed to examine whether children would fulfill their filial duty to help and support their parents during times of need despite the broken promise (Yeh & Yang, ).…”
Section: Filial Piety Among the Chinese: Traditional And Contemporarymentioning
confidence: 99%